Impact of physicochemical characteristics on the techno-functional properties of milk and whey protein dried powders - Letícia Ribeiro Barbosa; Carolina Neves Cunha; Caroline Barroso dos Anjos Pinto; Elisa Reis Silva de Oliveira; Maria Esther Leal da Silva Sad; Juliana de Carvalho da Costa; Rodrigo Stephani; Ítalo Tuler Perrone; Mirian Pereira Rodarte (International Dairy Journal, 2026)

Effect of the genetic merit for backfat thickness on the meat quality of steers - Thiago Luís Alves Campos de Araújo; Gelson Luís Dias Feijó; Marina de Nadai Bonin Gomes; Elzania Sales Pereira; Gilberto Romeiro de Oliveira Menezes; Ériklis Nogueira; Luiz Orcírio Fialho de Oliveira; Andrei Pereira Neves; Jaqueline Rodrigues Ferreira; Karla Izidio Latta; Douglas Gomes Vieira; Rodrigo da Costa Gomes (Tropical Animal Health and Production, 2026)
The objective of the present study was to evaluate the effects of the genetic merit for backfat thickness (GMB) and subcutaneous fat thickness (FT) on meat quality traits of Nellore and crossbred (½ Aberdeen Angus + ½ Nellore) steers. The animals were obtained by mating Nellore cows with Nellore or Aberdeen Angus bulls. Both paternal genetic groups were selected to provide positive (+, high GMB) or negative (-, low GMB) expected progeny differences (EPDs) in terms of backfat thickness. Two hundred and fourteen animals were obtained, reared on a pasture, and finished either in feedlot or semi-confinement systems. The steers were slaughtered, and the backfat visual scores, FT, marbling visual scores and meat color aspects were evaluated for the carcasses (24 h postmortem). In non-aged and aged meat samples (for 14 days), the pH, color, drip loss, cooking loss, and shear force were analyzed. The moisture content and intramuscular fat concentrations of the meat were determined. A second experimental approach was proposed to assess the influence of the FT class (low = 3.66 ± 0.58 mm; medium = 4.99 ± 0.49 mm and high = 6.81 ± 1.06 mm) on the same variables as in the original study. The GMB influenced ( P < 0.05) the FT and carcass fattening but did not influence ( P > 0.05) the physicochemical traits or the fat content of the meat. Steers with a low, medium, or high FT provided meats with similar physicochemical attributes. Thus, GMB increases subcutaneous fat deposition without affecting meat quality traits.

Circulating Matrix Metalloproteinase Activity and Functional Capacity in Individuals Undergoing Hemodialysis: Exploratory Findings from a Resistance Training Trial - Hugo de Luca Correa; Rafael Lavarini dos Santos; Ivo Vieira Sousa de Neto; Rodrigo Vanerson Passos Neves; Thaís Amaral Ferreira Baracho; Taynah Oliveira Martins; Jéssica Mycaella da Silva Barbosa; Thaís Branquinho de Araújo; Leandro Lima Sousa; Rebecca Salomão; Rita de Cássia Marqueti; Lysleine Alves de Deus; et al. (Journal of Science in Sport and Exercise, 2026)
Purpose To investigate the effects of 24 weeks of resistance training (RT) on pro- and active matrix metalloproteinases (MMPs) and their association with functional performance in end-stage kidney disease (ESKD) patients undergoing hemodialysis. Methods Forty-two ESKD patients (mean age: 65 ± 4 years; dry body mass: 71 ± 16 kg; body mass index: 25 ± 3 kg/m 2 ) were randomized into two groups: the control (CTL, n = 20) and RT group ( n = 22). RT was comprised three times per week for 24 weeks. Plasma MMP-2 and MMP-9 activity were assessed by zymography. Functional and body-composition outcomes included handgrip strength, fat-free mass (FFM), 5-min walking test, and the Timed Up and Go (TUG) test. Results Using bioinformatics tools, we found that MMP-2 gene expression in PBMCs was decreased in ESKD patients undergoing hemodialysis. At post-intervention, RT displayed a higher active MMP-2 activity, while MMP-9 did not change. After baseline adjustment, the estimated effect of RT on active MMP-2 was attenuated, whereas active MMP-9 showed a lower adjusted response in the RT group. Active MMP-2 activity was positively associated with handgrip strength, FFM ( P P Conclusion RT improved functional outcomes and the complex effects of RT on MMPs should be thoroughly investigated in future experimental and clinical studies.

Leaf traits and extrafloral nectaries: strategies to reduce herbivory in Cerrado woody species - Marina Neves Delgado; Jhonathan Oliveira Silva; Rogério dos Reis Mendonça; Vivivane Evangelista dos Santos Abreu; Sonia Nair Báo; Davi Rodrigo Rossatto (Flora, 2026)

Artificial reefs as functional substitutes? insights from a nine-year reef fish monitoring in Madeira - Pedro Neves; Rodrigo Riera; Cláudia Ribeiro (Biodiversity and Conservation, 2026)
Artificial reefs are widely deployed to mitigate natural reef degradation, yet their capacity to replicate the functional structure of natural reefs remains poorly understood. Using long-term underwater visual census data (2016–2024) from Madeira and Porto Santo Islands (NE Atlantic), we compared reef fish assemblages on shipwreck artificial reefs and natural rocky reefs through a functional trait–based framework. We quantified multiple dimensions of functional diversity, including functional richness, dispersion, specialization, redundancy, vulnerability, and functional beta diversity, and assessed temporal trajectories across reef types. Natural reefs consistently occupied a larger proportion of functional trait space than artificial reefs, reflecting broader representation of ecological roles. Functional beta diversity was dominated by nestedness, with artificial reefs generally supporting subsets of the regional functional pool. Temporal analysis revealed no evidence of progressive convergence of artificial reefs toward the functional structure of natural reefs over nearly a decade. Island context strongly modulated outcomes: in species-rich Madeira, functional structure was relatively homogeneous across reef types, whereas in Porto Santo, artificial reefs supported higher functional diversity than a heavily fished natural reef. Functional redundancy was low and functional vulnerability high across all assemblages, indicating limited buffering capacity against species loss. These results demonstrate that shipwrecks act as context-dependent complements rather than functional substitutes for natural reefs and highlight the value of functional approaches for evaluating artificial reef performance under ongoing reef degradation.

Reassessing and Updating Regulatory Standards on the Declaration of Storage Conditions in the Product Information of Medicinal Products: An Evidence-Based Proposal under EMA Guidance - Helena Pericão; Henrique Cavaco; Miguel Dias; Luís Sarmento; Mário Magalhães; Bernardo Filipe; Herivelto Vieira; João Rita; Pedro Gonçalves; Matilde Vaz; Beatriz Coimbra; Beatriz Monteiro; et al. (Pharmaceutical Research, 2026)
Purpose The European Medicines Agency (EMA) guideline Declaration of Storage Conditions in the Product Information of Medicinal Products (CPMP/QWP/609/96/Rev.2) was last revised in 2007. Since then, advances in stability science, increased climatic variability, and evolving regulatory expectations have highlighted limitations in the framework, particularly the use of vague descriptors such as “room temperature” or “no special storage conditions.” This work reassesses the scientific and regulatory basis for storage statements, integrating current understanding of mean kinetic temperature (MKT), climate-related risks, and developments in ICH and WHO guidance, and proposes a harmonized revision (Rev.3). Methods A structured analysis of regulatory and scientific principles was conducted, incorporating MKT, climate-related risks, and developments in ICH and WHO guidance. These elements informed a revised framework and model storage statements, including a decision table linking stability outcomes to label statements. Results The proposed update introduces explicit temperature-based statements, strengthens the linkage between stability data and label wording, clarifies requirements for moisture- and light-sensitive products, expands guidance for sterile and reconstituted preparations, and provides contingency instructions for temperature excursions. A decision table mapping stability outcomes to label statements is included to support regulatory implementation. Conclusion This revision provides an updated synthesis of EMA, ICH, and WHO requirements, translating regulatory principles into clear storage statements and contingency guidance. It offers a more precise framework reducing ambiguity, supports justification of storage conditions through stability data and MKT-informed risk assessment, aiming to improve understanding among patients and healthcare professionals, strengthening real-world product quality and contributing to future EMA guideline development. Highlights Identifies scientific and regulatory limitations in current “no special storage conditions” terminology; Links ICH stability guidelines and climatic variability to precise storage statements; Proposes harmonised core label phrases for room temperature, fridge, and freezer; Introduces contingency labelling for climate-related and cold-chain excursions.

Leaf phenology and functional traits interplay along an aridity gradient in tropical dry forests - Paulo Sérgio Santos-Neves; Sâmia Paula Santos Neves; Grênivel Mota da Costa; Pedro Manuel Villa; Davi Rodrigo Rossatto; Ligia Silveira Funch (Journal of Arid Environments, 2026)

Taxonomic uncertainty: causes, consequences, and metrics - Leila Meyer; Richard J. Ladle; Rafaela J. Trad; Annelise Frazão; Lívia Frateles; Thainá Lessa; Rafael B. Pinto; Tiago M.S. Freitas; Geiziane Tessarolo; Jhonny J.M. Guedes; Rodrigo A. Castro-Souza; Herison Medeiros; et al. (Trends in Ecology & Evolution, 2026)

Sustainable oxygen-functionalized graphitic carbons from agro-waste: Influence of biomass source on atenolol removal - Nathália Magno Galdino; Mayara Bitencourt Leão; Rodrigo Morawski; Alexandre G. Brolo; Andreia Neves Fernandes; Jacqueline Ferreira Leite Santos (Journal of Environmental Chemical Engineering, 2026)

Synergistic co-substrate effects in solid-state bioprocess of decomposing wood sawdust and agricultural wastes by Lichtheimia ramosa for protein enrichment, carbon reduction and enhanced enzymatic activity - Kemylli Farinon; César Barato; Jane Mary Lafayette Neves Gelinski; Rodrigo Simões Ribeiro Leite; Gustavo Graciano Fonseca (Biomass and Bioenergy, 2026)

Comparative analysis of sterile and non-sterile solid-state bioprocessing using Lichtheimia ramosa for agro-industrial waste valorization - Kemylli Farinon; César Milton Barato; Alison Likoski Neves; Rodrigo Simões Ribeiro Leite; Jane Mary Lafayette Neves Gelinski; Gustavo Graciano Fonseca (Bioresource Technology, 2026)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Kinetics of Vitamin C degradation and browning index of enriched heat-treated yogurt milk - Carolina Neves Cunha; Caroline Barroso dos Anjos Pinto; Maria Esther Leal da Silva Sad; Rodrigo Stephani; Alan Wolfschoon Pombo; Juliana de Carvalho da Costa; Ítalo Tuler Perrone (International Dairy Journal, 2025)

Numerical Study of an Oscillating Submerged Horizontal Plate Wave Energy Converter on the Southern Coast of Brazil: Parametric Analysis of the Variables Affecting Conversion Efficiency - Rodrigo Costa Batista; Elizaldo Domingues dos Santos; Luiz Alberto Oliveira Rocha; Mateus das Neves Gomes; Liércio André Isoldi (Journal of Marine Science and Engineering, 2025)
The utilization of ocean wave energy through environmentally sustainable technologies plays a pivotal role in the transition toward renewable energy sources. Among such technologies, the Submerged Horizontal Plate (SHP) stands out as a viable option for clean power production. This study focuses on the system’s application in a region on the southern coast of Brazil, identified as a potential site for future installation. To investigate this system, a three-dimensional numerical wave tank was developed to simulate wave behavior and hydrodynamic loads using the Navier–Stokes framework in the computational fluid dynamics software ANSYS FLUENT 2022 R2. The volume of fluid approach was adopted to track the free surface. The setup for wave generation in the numerical wave tank was verified against analytical solutions to ensure precision and validated under the SHP’s non-oscillating condition. To represent the oscillating condition, boundary conditions constrained motion along the x- and y-axes, allowing movement exclusively along the z-axis. A parametric analysis of 54 cases, with varying geometric configurations, wave characteristics, and submersion depths, indicated that the oscillating SHP configuration elongated perpendicular to wave propagation, combined with specific wave conditions, achieved a theoretical mean efficiency of 76.61%.

Translational insights into statin-induced myotoxicity: Differential impact of lipophilic and hydrophilic statins on iPSC-derived skeletal muscle cells from patients with familial hypercholesterolemia - Raul Hernandes Bortolin; Felipe de Souza Leite; Andre Ducati Luchessi; Joyce Esposito; Igor Neves Barbosa; Renata Caroline Costa de Freitas; Abhijeet Rajendra Sonawane; Sasha Anna Singh; Elena Aikawa; Kayque Alves Telles-Silva; Thiago Dominguez Crespo Hirata; Antonia Pereira Rosa Neta; et al. (Toxicology, 2025)

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

An exploratory study on the association between air pollution and health problems (ICD-10) with an emphasis on respiratory diseases - Ronan Adler Tavella; Julia Oliveira Penteado; Rodrigo de Lima Brum; Alicia da Silva Bonifácio; Meister Coelho San Martin; Elizabet Saes-Silva; Aline Neutzling Brum; Romina Buffarini; Washington Luiz Félix Correia Filho; Diana Francisca Adamatti; Rosália Garcia Neves; Edmilson Dias de Freitas; et al. (Atmospheric Pollution Research, 2025)

Alternative feedstocks for sustainable aviation fuels: Assessment of sugarcane-derived microbial oil - Andressa Neves Marchesan; Isabelle Lobo de Mesquita Sampaio; Mateus Ferreira Chagas; Wesley Cardoso Generoso; Thayse Aparecida Dourado Hernandes; Edvaldo Rodrigo Morais; Tassia Lopes Junqueira (Bioresource Technology, 2025)

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

How do the BRICS approach sustainable concerns? A systematic literature review - Cleiton Hluszko; Diego Alexis Ramos Huarachi; Micaela Ines Castillo Ulloa; Rodrigo Salvador; Fabio Neves Puglieri; Antonio Carlos de Francisco (Environmental Development, 2024)

Supplementation of high doses of vitamin D during the gestational period do not cause reproductive, teratogenic and genotoxic damage in mice - Silvia Cordeiro das Neves; Sarah Alves Auharek; Roberto da Silva Gomes; Marcelo Luiz Brandão Vilela; Valter Aragão do Nascimento; Henrique Rodrigues Scherer Coelho; Karuppusamy Arunachalam; Andréia Conceição Milan Brochado Antoniolli-Silva; Rodrigo Juliano Oliveira (Food and Chemical Toxicology, 2024)

Reproductive phenology of the non-woody community in a seasonally dry tropical forest and woodland in northeastern Brazil - Sâmia Paula Santos Neves; Adelly Cardoso de Araujo Fagundes; Alexsandro Bezerra-Silva; Paulo Sérgio Neves dos Santos; David Rodrigo Rossatto; Lia d’Afonsêca Pedreira de Miranda; Ligia Silveira Funch (Journal of Arid Environments, 2024)

Influence of micro and nanofibrillated cellulose on sweetened yogurt production and storage - Carolina Neves Cunha; Caroline Barroso dos Anjos Pinto; Maria Esther Leal da Silva Sad; Vitória Maria Medalha Colturato; Gabriela Leila Berto; Valdeir Arantes; Hernane da Silva Barud; Rodrigo Stephani; Ítalo Tuler Perrone (International Dairy Journal, 2024)

Blood and CSF anti-neuronal antibodies testing in psychotic syndromes: a retrospective analysis from a tertiary psychiatric hospital - Joana Lopes; Maria João Malaquias; Joana Freitas; Rodrigo Valido; Paula Carneiro; Esmeralda Neves; Ana Maria Moreira; Raquel Samões; Ernestina Santos; Ana Paula Correia (Immunologic Research, 2024)

Salt tolerance and survival of the freshwater bioinvasive gastropod Melanoides tuberculata (Thiariidae): when different methodologies tell us different stories - Riccardo Mugnai; Shirley Reis de Oliveira; Eduardo Mariano-Neto; Rodrigo Johnsson; Elizabeth Neves (Molluscan Research, 2024)

Exploring uncharted waters: insights into groundwater zooplankton of the Brazilian semiarid region - Carolina Teixeira Puppin-Gonçalves; Diego Medeiros Bento; Gilmar Perbiche-Neves; Rodrigo Lopes Ferreira; Marconi Souza-Silva; Vanessa Becker; Juliana Déo Dias (Aquatic Sciences, 2024)

Eco-friendly and high-performance extraction of flavonoids from lemon peel wastes by applying ultrasound-assisted extraction and eutectic solvents - Jaísa O. Chaves; Leonardo M. de Souza Mesquita; Monique M. Strieder; Leticia S. Contieri; Rodrigo S. Pizani; Vitor L. Sanches; Juliane Viganó; Rosangela M. Neves Bezerra; Mauricio A. Rostagno (Sustainable Chemistry and Pharmacy, 2024)

Feline leishmaniasis in an animal shelter in northeastern Brazil: Clinical aspects, coinfections, molecular detection, and serological study of a new recombinant protein - Luiz Fernando de Jesus Nascimento; Ana Carolina Amado-Gomes; Filipe Dantas-Torres; Fred Luciano Neves Santos; Wemerson de Santana Neres; Pedro Estevão de Souza Filho; Mariana Tibúrcio Santos; José Rodrigo Santos Silva; Cláudia Fideles Resende; Jenner Karlisson Pimenta dos Reis; Sona Jain; João Luís Reis Cunha; et al. (Research in Veterinary Science, 2024)

Stemphylium lycopersici immobilized in polyurethane (PU) treated in pressurized fluid CO2 as biocatalyst for ω-transamination reactions - Maria Sandra Ramos Queiroz; Nádia Ligianara Dewes Nyari; Carolina Lixa Victor Neves; Anderson de Sá Pinheiro; Marcelo Luis Mignoni; Rogério Marcos Dallago; Rodrigo Otávio Mendonça Alves de Souza; Denise Oliveira Guimarães; Ivana Correa Ramos Leal (Biocatalysis and Agricultural Biotechnology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Carcass characteristics and meat quality of cull cows from different genetic groups - Karla Izidio Latta; Luís Carlos Vinhas Ítavo; Rodrigo da Costa Gomes; Marina de Nadai Bonin Gomes; Jaqueline Rodrigues Ferreira; Andrei Pereira Neves; Thiago Alves Campos de Araujo; Gelson Luís Dias Feijó; Gilberto Romeiro de Oliveira Menezes (Livestock Science, 2024)

Pressurized liquid extraction assisted by high-intensity ultrasound to obtain hesperidin from lime waste: Integration of in-line purification and on-line chromatographic analysis - Vitor L. Sanches; Monique Martins Strieder; Marcia Cristina Breitkreitz; Rosângela Maria Neves Bezerra; Jaísa O. Chaves; Isadora Lopes de Oliveira; Leonardo M. de Souza Mesquita; Juliane Viganó; Letícia Sanches Contieri; Rodrigo Stein Pizani; Maurício A. Rostagno (Food Research International, 2024)

Predicting effluent quality parameters for wastewater treatment plant: A machine learning-based methodology - João Vitor Rios Fuck; Maria Alice Prado Cechinel; Juliana Neves; Rodrigo Campos de Andrade; Ricardo Tristão; Nicolas Spogis; Humberto Gracher Riella; Cíntia Soares; Natan Padoin (Chemosphere, 2024)

Absence of adverse effects of Blutaparon portulacoides (A.St.-Hil.) Mears in mice exposed during pregnancy - Silvia Cordeiro das Neves; Renata Coelho Rodrigues Noronha; Antonio Carlos Duenhas Monreal; Luís Adriano Santos do Nascimento; Adauto Lima Cardoso; Flávia dos Santos Tavares; Bethânia Borges Tura; Roberto da Silva Gomes; Candida Aparecida Leite Kassuya; Viktor Krejci Nunes; Marcos José Salvador; Rodrigo Juliano Oliveira (South African Journal of Botany, 2024)

Lost life expectancy following a hypothetical urban radiological incident - Suzana C.T. Neves; Luis R.P. Horta; Rodrigo V. Machado; Danielle E.G. Furuya; Pollyana S. Shimada; Alba R.A. Arana; Ana Paula A. Favareto; Edson R. Andrade (Journal of Environmental Radioactivity, 2024)

Association of rainfall pattern with the disappearance of mineral mixtures fed cattle managed on tropical pastures - Zey Welington Gomes de Souza; Manoel Gustavo Paranhos da Silva; Andrei Pereira Neves; Thiago Luís Alves Campos de Araújo; Nickson Milton Correa Siqueira; Wallyson Almeida Amaral; Denise Baptaglin Montagner; Luís Carlos Vinhas Ítavo; Valter Bumbieris Júnior; Bruno Marson; Márcio de Nadai Bonin; Rodrigo da Costa Gomes (Tropical Animal Health and Production, 2024)

Zooplankton studies warn abnormal protrusions on the copepods from coastal environments under anthropic impacts - Christiane Sampaio de Souza; Paulo de Oliveira Mafalda Júnior; Sigrid Neumann-Leitão; Amilcar Farias; Rodrigo Johnsson; Elizabeth Gerardo Neves (Regional Studies in Marine Science, 2024)

Enhancing wastewater treatment efficiency through machine learning-driven effluent quality prediction: A plant-level analysis - Maria Alice Prado Cechinel; Juliana Neves; João Vitor Rios Fuck; Rodrigo Campos de Andrade; Nicolas Spogis; Humberto Gracher Riella; Natan Padoin; Cintia Soares (Journal of Water Process Engineering, 2024)

Endophytic colonization of five Trichoderma species and their effects on growth of a Eucalyptus hybrid - Jéssica Bezerra Bandeira; Jovielly Neves Rodrigues; Rodrigo Silva de Oliveira; Ismael Oliveira Pinto; Aloísio Freitas Chagas-Júnior; Vitor L. Nascimento; Maíra Ignacio Sarmento; Cristiano Bueno de Moraes; Renato Almeida Sarmento (Brazilian Journal of Microbiology, 2023)

A new blue Astrangia coral (Scleractinia) from the Southwestern Atlantic - Saulo Serra; Elizabeth Gerardo Neves; Jessika Alves; Rodrigo Johnsson (Marine Biodiversity, 2023)

Investigating the effects of mesotrione/atrazine-based herbicide on honey bee foragers - Renan dos Santos Araújo; Thaís Andrade Viana; Lorena Lisbetd Botina; Daniel Silva Sena Bastos; Beatriz Cristina da Silva Alves; Mariana Machado-Neves; Rodrigo Cupertino Bernardes; Gustavo Ferreira Martins (Science of The Total Environment, 2023)

Social isolation leads to mild social recognition impairment and losses in brain cellularity - Daniel Menezes Guimarães; Bruna Valério-Gomes; Rodrigo Jorge Vianna-Barbosa; Washington Oliveira; Gilda Ângela Neves; Fernanda Tovar-Moll; Roberto Lent (Brain Structure and Function, 2023)

A new genus of Aoridae and a new species of Bemlos Shoemaker, 1925 (Amphipoda: Senticaudata) from Northeastern Brazil - Jessika Alves; Marcos Moura Nogueira; Elizabeth G. Neves; Rodrigo Johnsson (Marine Biodiversity, 2023)

Evaluation of different platelet-rich plasma protocols for use in the equine reproductive clinic - Joel N De Oliveira; Henrique Ba Bastos; Veronica LC Bueno; Gustavo R Larentis; Rodrigo C Mattos; Adriana P Neves (Journal of Equine Veterinary Science, 2023)

A review of 121 years of studies on the freshwater zooplankton of Brazil - Maria Stela Maioli Castilho-Noll; Gilmar Perbiche-Neves; Natan Guilherme dos Santos; Leilane Talita Fatoreto Schwind; Fernando Miranda Lansac-Tôha; Alan Cleber Santos da Silva; Bianca Ramos de Meira; Ciro Yoshio Joko; Cláudio Simões de Morais-Júnior; Edissa Emi Cortez Silva; Eneida Maria Eskinazi-Sant'Anna; Felipe Rafael Oliveira; et al. (Limnologica, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Emergence Response of Telenomus podisi (Hymenoptera: Scelionidae) to Field Temperature Originated from Colonies Reared at Different Temperature Regimes - Fernanda Caroline Colombo; Rodrigo Mendes Antunes Maciel; Matheus Deniz; Pedro Manuel Oliveira Janeiro Neves; Adeney de Freitas Bueno (Neotropical Entomology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

N-acetylation of toxic aromatic amines by fungi: Strain screening, cytotoxicity and genotoxicity evaluation, and application in bioremediation of 3,4-dichloroaniline - Amanda Dal’Ongaro Rodrigues; Arthur dos Santos Montanholi; Angela Akimi Shimabukuro; Murilo Kioshi Aquino Yonekawa; Nadla Soares Cassemiro; Denise Brentan Silva; Clarice Rossato Marchetti; Carlos Eduardo Weirich; Adilson Beatriz; Fabiana Fonseca Zanoelo; Maria Rita Marques; Giovana Cristina Giannesi; et al. (Journal of Hazardous Materials, 2023)

Morphological characteristics and yield of Opuntia stricta and Nopalea cochenillifera in integrated crop systems with caatinga trees - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Cleber Medeiros Barreto; Marcos Neves Lopes; Magno José Duarte Cândido (Agroforestry Systems, 2023)

The Ground-Dwelling Ant Fauna from a Cerrado Reserve in Southeastern Brazil: Vegetation Heterogeneity as a Promoter of Ant Diversity - Heraldo Luis Vasconcelos; Rodrigo Machado Feitosa; Giselda Durigan; Ruthe Emilia Oliveira Saraiva Leão; Karen Christina Ferreira Neves (Neotropical Entomology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Framework for Improving Land Boundary Conditions in Ocean Regional Products - Francisco Campuzano; Flávio Santos; Lucian Simionesei; Ana R. Oliveira; Estrella Olmedo; Antonio Turiel; Rodrigo Fernandes; David Brito; Marco Alba; Antonio Novellino; Ramiro Neves (Journal of Marine Science and Engineering, 2022)
The coupling of coastal or regional ocean models to hydrological models or observed data is currently an uncommon practice in operational oceanography. Though hydrological models are regarded as a powerful and useful tool for estimating the quantity and quality of freshwater running in a watershed, they fail to provide accurate results for river flow reaching the coastal area due to water-management activities occurring within the river catchment, activities such as human consumption, irrigation, storage, etc. For this reason, many coastal and regional ocean models continue to impose surface zero-salinity discharges as land boundary conditions for representing such a dynamic boundary. Moreover, river flows are based in climatologies, thus neglecting seasonal and interannual variability. To achieve those objectives, this study proposes an integrated methodology ranging from watershed models to validation in the coastal area and passing through methods and proxies for integrating the freshwater flows into regional ocean models. The main objective of this study is to explore the results obtained by using more sophisticated land boundary conditions based on the capacities of state-of-the-art hydrologic models combined with observation networks. In addition to the evaluation of the source of river-flow data, this work also explores the use of estuarine proxies based on simple modelling grids. The estuarine proxies enable the incorporation of the mixing processes that take place in estuaries into the land fluxes and obtain the plume momentum. The watershed, estuarine proxies, and ocean were modelled using the MOHID Water modelling system and evaluated in western Iberia waters. The modelling results served to illustrate the sea surface salinity extension of the Western Iberia Buoyant Plume (WIBP) during an extreme event in March 2018.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Climate change impact assessment on worldwide rain fed soybean based on species distribution models - João Rafael Silva Soares; Rodrigo Soares Ramos; Ricardo Siqueira da Silva; Daniel Victor Chaves Neves; Marcelo Coutinho Picanço (Tropical Ecology, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Leaf trait variability maintains similar leaf exchange rhythms in Hirtella glandulosa Spreng. (Chrysobalanaceae) populations growing on contrasting soil types in the Brazilian Atlantic Forest - Josevânia Carneiro de Oliveira; Marília Grazielly Mendes dos Santos; Sâmia Paula Santos Neves; Angela Pierre Vitória; Davi Rodrigo Rossatto; Lia d’Afonsêca Pedreira de Miranda; Ligia Silveira Funch (Brazilian Journal of Botany, 2021)

Essential and Potentially Toxic Elements from Brazilian Geopropolis Produced by the Stingless Bee Melipona quadrifasciata anthidioides Using ICP OES - Rodrigo da Cruz Ferreira; Fernanda de Souza Dias; Caroline de Aragão Tannus; Filipe Barbosa Santana; Daniele Cristina Muniz Batista dos Santos; Fábio de Souza Dias; Marina Siqueira de Castro; Hugo Neves Brandão; Aníbal de Freitas Santos Júnior; Lidércia Cavalcanti Ribeiro Cerqueira e Silva; Fábio Alexandre Chinalia (Biological Trace Element Research, 2021)

AMPAr GluA1 Phosphorylation at Serine 845 in Limbic System Is Associated with Cardiac Autonomic Tone - Hiago Murilo Melo; Cristiane Ribeiro de Carvalho; Alexandre Ademar Hoeller; Jefferson Luiz Brum Marques; Marcelo Neves Linhares; Mark William Lopes; Guilherme Loureiro Fialho; Peter Wolf; Katia Lin; Zuner A. Bortolotto; Jeremy M. Henley; André D’Ávila; et al. (Molecular Neurobiology, 2021)

Comparison of foliar spray and soil irrigation of biogenic CuO nanoparticles (NPs) on elemental uptake and accumulation in lettuce - Marcio Yukihiro Kohatsu; Milena Trevisan Pelegrino; Lucilena Rebelo Monteiro; Bruna Moreira Freire; Rodrigo Mendes Pereira; Paola Fincheira; Olga Rubilar; Gonzalo Tortella; Bruno Lemos Batista; Tatiane Araujo de Jesus; Amedea Barozzi Seabra; Camila Neves Lange (Environmental Science and Pollution Research, 2021)

Effects of stocking density on survival, growth and stress resistance of juvenile tambaqui (Colossoma macropomum) reared in a recirculating aquaculture system (RAS) - Walisson de Souza e Silva; Andre Lima Ferreira; Luanna do Carmo Neves; Nathália Soares Ferreira; Glauber David Almeida Palheta; Rodrigo Takata; Ronald Kennedy Luz (Aquaculture International, 2021)

Rhinergasilus unguilongus n. sp. (Copepoda: Ergasilidae): A Gill Parasite of the Freshwater Fish Prochilodus lineatus (Valenciennes, 1837) (Actinopterygii: Prochilodontidae) from the Neotropical Region, Brazil - Rodrigo Bravin Narciso; Gilmar Perbiche-Neves; Reinaldo José da Silva (Acta Parasitologica, 2021)

Intravenous infusion of bone marrow mononuclear cells promotes functional recovery and improves impaired cognitive function via inhibition of Rho guanine nucleotide triphosphatases and inflammatory signals in a model of chronic epilepsy - Zaquer Suzana Munhoz Costa-Ferro; Gutierre Neves de Oliveira; Daniele Vieira da Silva; Daniel Rodrigo Marinowic; Denise Cantarelli Machado; Beatriz Monteiro Longo; Jaderson Costa da Costa (Brain Structure and Function, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Benzocaine and menthol as anesthetics for the African cichlid Aulonocara nyassae - Andre Lima Ferreira; Walisson de Souza e Silva; Luanna do Carmo Neves; Nathália Soares Ferreira; Rodrigo Takata; Ronald Kennedy Luz (Aquaculture International, 2020)

5 km front crawl in pool and open water swimming: breath-by-breath energy expenditure and kinematic analysis - Rodrigo Zacca; Vânia Neves; Tiago da Silva Oliveira; Susana Soares; Luís Manuel Pinto Lopes Rama; Flávio Antônio de Souza Castro; João Paulo Vilas-Boas; David B. Pyne; Ricardo J. Fernandes (European Journal of Applied Physiology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A New Species of Rhinergasilus Boeger et Thatcher, 1988 (Copepoda: Ergasilidae) from Gills of Astyanax fasciatus (Cuvier, 1819) (Actinopterygii: Characidae) - Rodrigo Bravin Narciso; Heleno Brandão; Gilmar Perbiche-Neves; Reinaldo José da Silva (Acta Parasitologica, 2020)

A New Genus of Ergasilidae (Copepoda: Cyclopoida) from the Gills of Astyanax fasciatus (Cuvier, 1819) (Actinopterygii: Characidae) - Rodrigo Bravin Narciso; Heleno Brandão; Gilmar Perbiche-Neves; Reinaldo José da Silva (Acta Parasitologica, 2019)

Sustained mass coral bleaching (2016–2017) in Brazilian turbid-zone reefs: taxonomic, cross-shelf and habitat-related trends - Carolina D. Teixeira; Rodrigo L. L. Leitão; Felipe V. Ribeiro; Fernando C. Moraes; Leonardo M. Neves; Alex C. Bastos; Guilherme H. Pereira-Filho; Milton Kampel; Paulo S. Salomon; João A. Sá; Ludmilla N. Falsarella; Michelle Amario; et al. (Coral Reefs, 2019)

Optimization of Benzodiazepine Drugs Removal from Water by Heterogeneous Photocatalysis Using TiO2/Activated Carbon Composite - Deivisson L. Cunha; Alexei Kuznetsov; Joyce R. Araujo; Rodrigo S. Neves; Braulio S. Archanjo; Maria Cristina Canela; Marcia Marques (Water, Air, & Soil Pollution, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

A dark side of cleaning symbiosis: manned submersible observations - Rodrigo L. Moura; Fernando C. Moraes; Gilberto M. Amado-Filho; Leonardo M. Neves; Alexandre D. Kassuga; Danielle D’Agostini; Alex C. Bastos (Marine Biodiversity, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Unusual Intestinal Involvement by Paracoccidioidomycosis Diagnosed After Oral Manifestation - Rodrigo Neves-Silva; Patrícia Maria Fernandes; Alan Roger Santos-Silva; Pablo Agustin Vargas; Ricardo de Souza Cavalcante; Marcio Ajudarte Lopes (Mycopathologia, 2018)

Transferability of nuclear microsatellite markers to the atmospheric bromeliads Tillandsia recurvata and T. aeranthos (Bromeliaceae) - Cleber Juliano Neves Chaves; Felipe Aoki-Gonçalves; Bárbara Simões Santos Leal; Davi Rodrigo Rossatto; Clarisse Palma-Silva (Brazilian Journal of Botany, 2018)

Linking Biodiversity, the Environment and Ecosystem Functioning: Ecological Functions of Dung Beetles Along a Tropical Elevational Gradient - Cássio Alencar Nunes; Rodrigo Fagundes Braga; Fernando de Moura Resende; Frederico de Siqueira Neves; José Eugênio Cortes Figueira; G. Wilson Fernandes (Ecosystems, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Neotropical savanna ants show a reversed latitudinal gradient of species richness, with climatic drivers reflecting the forest origin of the fauna - Heraldo L. Vasconcelos; Jonas B. Maravalhas; Rodrigo M. Feitosa; Renata Pacheco; Karen C. Neves; Alan N. Andersen (Journal of Biogeography, 2018)
Aim To evaluate the extent to which ant species richness in Neotropical savannas varies with macrogeographic variables, and to identify the potential climatic drivers of such variation. Location The Cerrado savanna biome of central Brazil, in a region spanning ca. 20° of latitude and 18°of longitude. Methods Standardized sampling of the arboreal and ground‐dwelling faunas was performed in 29 well‐preserved savanna sites using pitfall traps. Species were classified according to their habitat affinities: open‐savanna specialists, forest‐associated species or habitat generalists. We used generalized linear models to evaluate the importance of geographic (latitude, longitude and elevation) and climatic (mean temperature and three metrics of rainfall) variables as predictors of species richness. Results The total number of species recorded at each site varied more than twofold (from 59 to 144), and latitude was the best geographic correlate of overall species richness. However, contrary to the expected pattern, more species were found at higher than lower latitudes. This reversed latitudinal pattern of diversity occurred for both the arboreal and ground‐dwelling faunas, and for the habitat generalists and forest specialists. The savanna specialists showed a mid‐latitudinal peak in diversity. Overall, there was a significant positive association between rainfall and species richness, but the strength of this relationship varied with ant habitat affinity. Main conclusions The Cerrado ant fauna shows a reverse latitudinal gradient in species diversity, and this can be explained by increasing rainfall during the warmest months of the year (and therefore in plant productivity) with increasing latitude. The sensitivity of Cerrado ant diversity to declining rainfall contrasts with the high resilience to aridity of the Australian savanna ant fauna, and this reflects the contrasting evolutionary histories of these faunas. Our findings highlight the importance of historical processes as drivers of intercontinental contrasts in macroecological patterns.

The roles of rainfall, soil properties, and species traits in flowering phenology along a savanna-seasonally dry tropical forest gradient - Sâmia Paula Santos Neves; Lia d´Afonsêca Pedreira de Miranda; Davi Rodrigo Rossatto; Ligia Silveira Funch (Brazilian Journal of Botany, 2017)

Compacted Multiparticulate Systems for Colon-Specific Delivery of Ketoprofen - Rodrigo Gomes de Alencar; Aline Carlos de Oliveira; Eliana Martins Lima; Marcílio Sérgio Soares da Cunha-Filho; Stephânia Fleury Taveira; Ricardo Neves Marreto (AAPS PharmSciTech, 2017)

Elevated CO2 improves growth, modifies anatomy, and modulates essential oil qualitative production and gene expression in Lippia alba (Verbenaceae) - Diego Silva Batista; Kamila Motta de Castro; Andréa Dias Koehler; Brenda Neves Porto; Anderson Rodrigo da Silva; Vinicius Carius de Souza; Maria Luisa Teixeira; Maria das Graças Cardoso; Marcelo de Oliveira Santos; Lyderson Facio Viccini; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Coupling watersheds, estuaries and regional ocean through numerical modelling for Western Iberia: a novel methodology - Francisco Campuzano; David Brito; Manuela Juliano; Rodrigo Fernandes; Hilda de Pablo; Ramiro Neves (Ocean Dynamics, 2016)

Synchronous Oral Paracoccidioidomycosis and Pulmonary Tuberculosis in an Immunocompetent Patient - Ana Carolina Amorim Pellicioli; Rodrigo Neves-Silva; Alan Roger Santos-Silva; Pablo Agustin Vargas; Márcio Ajudarte Lopes (Mycopathologia, 2015)

A new species of Troglocarcinus (Decapoda: Brachyura: Cryptochiridae) symbiotic with the Brazilian endemic coral Mussismilia (Anthozoa: Scleractinia: Mussidae) - Roberta Canário; Marcelle F. S. Badaró; Rodrigo Johnsson; Elizabeth G. Neves (Marine Biology Research, 2015)

Extrafloral nectary morphology and the role of environmental constraints in shaping its traits in a common Cerrado shrub (Maprounea brasiliensis A. St.-Hill: Euphorbiaceae) - Marina Neves Delgado; Sônia Nair Báo; Lourdes I. V. Amaral; Davi Rodrigo Rossatto; Helena Castanheira de Morais (Brazilian Journal of Botany, 2014)

A Single Neurotoxic Dose of Methamphetamine Induces a Long-Lasting Depressive-Like Behaviour in Mice - Carlos D. Silva; Ana F. Neves; Ana I. Dias; Hugo J. Freitas; Sheena M. Mendes; Inês Pita; Sofia D. Viana; Paulo A. de Oliveira; Rodrigo A. Cunha; Carlos A. Fontes Ribeiro; Rui D. Prediger; Frederico C. Pereira (Neurotoxicity Research, 2014)

The autonomous Simpatico system for real-time continuous water-quality and current velocity monitoring: examples of application in three Portuguese estuaries - Erwan Garel; Susana Nunes; João Magalhães Neto; Rodrigo Fernandes; Ramiro Neves; João Carlos Marques; Óscar Ferreira (Geo-Marine Letters, 2009)

Epidemiological and Clinical Aspects of the First Outbreak of Bovine Mastitis Caused by Prototheca zopfii in Goiás State, Brazil - Válter Ferreira Félix Bueno; Albenones José de Mesquita; Rodrigo Balduino Soares Neves; Marcos Almeida de Souza; Andréa Rentz Ribeiro; Edmar Soares Nicolau; Antônio Nonato de Oliveira (Mycopathologia, 2006)